Foot-and-Mouth Disease Virus: Stability of Neutralizing Antibody After Freeze-drying and Air-drying - Fellowes, Oliver N. (1969)
It is possible to stabilize foot-and-mouth disease antiserum by either freeze-drying in bottles or air-drying on paper for periods of 7 months.